2021
DOI: 10.1108/bfj-12-2020-1121
|View full text |Cite
|
Sign up to set email alerts
|

Does a healthy diet travel? Motivations, satisfaction and loyalty with plant-based food dining at destinations

Abstract: PurposeThe research objectives were to: (1) examine the relationship among motivations, satisfaction and loyalty with plant-based food dining at destinations; (2) determine if and how the attractiveness of eating plant-based foods moderates satisfaction and loyalty; and (3) investigate potential differences in visitor background information and consumption characteristics.Design/methodology/approachA survey was conducted at tourist attractions in southern Taiwan and 274 valid questionnaires were obtained. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Shashi and Singh (2015) showed that biodiversity preservation, conservation of natural resources and lower energy consumption play key roles in influencing consumer purchasing intentions towards organic foods. Chang et al's (2021) study on plant‐based diets found that the presence of restaurants offering plant‐based dining in a certain destination acts as an important motivation for travelers. Shin et al (2017) demonstrated a similar relationship between tourists' intention to visit and willingness to pay for a certain restaurant providing a menu based on foods that are respectful of the environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Shashi and Singh (2015) showed that biodiversity preservation, conservation of natural resources and lower energy consumption play key roles in influencing consumer purchasing intentions towards organic foods. Chang et al's (2021) study on plant‐based diets found that the presence of restaurants offering plant‐based dining in a certain destination acts as an important motivation for travelers. Shin et al (2017) demonstrated a similar relationship between tourists' intention to visit and willingness to pay for a certain restaurant providing a menu based on foods that are respectful of the environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Most studies have focused on the environmental dimension of sustainable food consumption. This has received a lot of attention in the marketing and consumption arena, including the tourism context (Cachero‐Martínez, 2020; Chang et al, 2021; Dalmoro et al, 2020; Nam, 2020; Rothwell et al, 2016; Shashi & Singh, 2015; Shin et al, 2017). Shashi and Singh (2015) showed that biodiversity preservation, conservation of natural resources and lower energy consumption play key roles in influencing consumer purchasing intentions towards organic foods.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research on land restaurants show how food and dining experiences affect travellers' behaviour, like their revisit behaviour (Bjo ¨rk and Kauppinen-Ra ¨isa ¨nen, 2016), overall satisfaction and even travel satisfaction (Chang et al, 2021). Specifically, travellers' revisit intentions relate to restaurant satisfaction for both fast food and full-service land restaurants (Slack et al, 2021).…”
Section: Effect Of Dining Behaviour On Overall Dinescape and Cruise V...mentioning
confidence: 99%
“…Tourism industry aims to provide positive and memorable travel experiences (Ritchie et al , 2011) and food is a key source of such experiences (Björk and Kauppinen-Räisänen, 2016). Research on land restaurants show how food and dining experiences affect travellers’ behaviour, like their revisit behaviour (Björk and Kauppinen-Räisänen, 2016), overall satisfaction and even travel satisfaction (Chang et al , 2021). Specifically, travellers’ revisit intentions relate to restaurant satisfaction for both fast food and full-service land restaurants (Slack et al , 2021).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…Looking more widely across the hospitality industry, a variety of research themes can be identified, though the work on plant-based food within the industry is fragmented and it lacks a coherent framework. Drawing their empirical information from Taiwan, Chang et al (2021) looked to examine the relationship among motivations, satisfaction and loyalty with plant-based food dining at destinations, and to determine if, and how, the attraction of plant-based dining moderated customer satisfaction and loyalty. The authors found that a positive relationship between motivations and satisfaction and loyalty in plant-based food dining, and motivations were found to comprise physical, cultural, interpersonal and prestige domains, while satisfaction and loyalty had three dimensions, namely overall satisfaction, intention to revisit, and intention to recommend.…”
Section: Cameo Literature Reviewmentioning
confidence: 99%